2015
DOI: 10.1088/1741-2560/12/6/066007
|View full text |Cite
|
Sign up to set email alerts
|

Identification of redundant and synergetic circuits in triplets of electrophysiological data

Abstract: Abstract.Objective. Neural systems are comprised of interacting units, and relevant information regarding their function or malfunction can be inferred by analyzing the statistical dependencies between the activity of each unit. Whilst correlations and mutual information are commonly used to characterize these dependencies, our objective here is to extend interactions to triplets of variables to better detect and characterize dynamic information transfer. Approach. Our approach relies on the measure of interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
(60 reference statements)
0
19
0
Order By: Relevance
“…Despite some theoretical advances [25, 3845], a theory for the origin of the nucleation centers of network spikes, enabling prediction of the number and locations of primary nucleation centers before carrying out the dynamic simulations, is currently absent. We have excluded the influence of fluctuations of the spatial distribution density of neurons by placing the neurons strictly periodically in the nodes of a square lattice - the nucleation centers still occurred (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some theoretical advances [25, 3845], a theory for the origin of the nucleation centers of network spikes, enabling prediction of the number and locations of primary nucleation centers before carrying out the dynamic simulations, is currently absent. We have excluded the influence of fluctuations of the spatial distribution density of neurons by placing the neurons strictly periodically in the nodes of a square lattice - the nucleation centers still occurred (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Section 3 focuses on the application of information partitioning to time-series data sets. While the information partitioning approach has been applied to time-series data in neural and cardiovascular applications [Erramuzpe et al, 2015;Faes et al, 2015], these have assumed either Gaussianity or simple fixed binning pdf estimation techniques, and use the prevalent approach based on minimum mutual information. When working with environmental time series data, we need robust methods to handle noise or observational errors, atom-at-zero effects for mixed distributions and characterization of statistical significance of measures.…”
Section: Introductionmentioning
confidence: 99%
“…Interaction information (II) quantifies in triplets of variables the amount of redundant (positive interaction) or synergetic (negative interaction) information contained in the triplet [1,2]. While the mutual information (MI) shared between two variables is always positive or zero (for the case of independent variables), II can be either positive or negative, respectively, unveiling redundancy (R) or synergy (S).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of synergetic effects is well-known to occur in sociological and psychological modeling, where (very often) there are some variables that increase the prediction power on different ones [5]. On the other hand, redundancy have been addressed before in gene regulatory networks [6,7] and electrophysiological data in patients with epilepsy [2] or with deficit of consciousness [8], but, the pattern of triplet interactions in functional magnetic resonance imaging is not yet well-understood. By using a different methodology based on Granger causality influence, the authors in [9] found that R regions occurred mainly due to voxel-contiguity and inter-hemispheric symmetry, while S occurred mainly between non-homologous region pairs in contra-lateral hemispheres.…”
Section: Introductionmentioning
confidence: 99%